2011
DOI: 10.1111/j.1399-5448.2011.00834.x
|View full text |Cite
|
Sign up to set email alerts
|

FTO gene is related to obesity in Chilean Amerindian children and impairs HOMA-IR in prepubertal girls

Abstract: In summary, we confirm the association of the FTO gene single-nucleotide polymorphism rs9939609 with obesity in Chilean Amerindian children. Furthermore we show an association between the risk allele (A) and insulin resistance-related markers in prepubertal obese girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
2
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 42 publications
1
19
2
9
Order By: Relevance
“…Africa is an especially important continent to study because of its complex population history, which results in high levels of genetic and phenotypic variation. The FTO obesity association is well established in populations of Caucasian ancestry (14,98–112) as well as in Asians (19,113–135), and consistent findings have also been documented in other ethnicities such as populations from Australia (136) and South America (137–139). However, studies conducted so far in African populations (Table 1) have frequently reported negative findings.…”
Section: What Have Studies In Divergent Ethnic Population Told Us?mentioning
confidence: 57%
See 1 more Smart Citation
“…Africa is an especially important continent to study because of its complex population history, which results in high levels of genetic and phenotypic variation. The FTO obesity association is well established in populations of Caucasian ancestry (14,98–112) as well as in Asians (19,113–135), and consistent findings have also been documented in other ethnicities such as populations from Australia (136) and South America (137–139). However, studies conducted so far in African populations (Table 1) have frequently reported negative findings.…”
Section: What Have Studies In Divergent Ethnic Population Told Us?mentioning
confidence: 57%
“…The FTO obesity association is well established in populations of Caucasian ancestry (14,(98)(99)(100)(101)(102)(103)(104)(105)(106)(107)(108)(109)(110)(111)(112) as well as in Asians (19,, and consistent findings have also been documented in other ethnicities such as populations from Australia (136) and South America (137)(138)(139). However, studies conducted so far in African populations ( (147) and presented strong evidence for an association between BMI and rs3751812.…”
Section: Obesity Reviewsmentioning
confidence: 72%
“…In the first genetic studies on children with obesity, the relationship between the FTO rs9939609 polymorphism and body weight was indicated in girls but not in boys . Moreover, the FTO rs9939609 polymorphism is associated with higher homeostasis model assessment index in girls before puberty, but not in boys , although further studies, including ours, did not confirm these sex‐associated effects.…”
Section: Relationships Between Genetic Polymorphisms and Cardiovasculmentioning
confidence: 81%
“…Further adjustment for BMI and age did not alter the result, but the level of significance was reduced. [68] In contrast, the association was not observed among normal weight girls or the normal weight or obese boys.…”
Section: The Effect Of Fat Mass and Obesity-associated On Glucose Hommentioning
confidence: 95%